The contribution of civil society to sustainable development in the Gulf and beyond. Issue 5 (4th July 2019) - Hayman, Rachel
ABSTRACT: Numerous countries across the Arab region are linking national development visions and strategies to the Sustainable Development Goals (SDGs). This offers potential opportunities for civil society organisations to push their agendas and build their capacity. Building on a presentation given in Qatar in March 2018, this viewpoint identifies four ways that civil society in the Gulf and other Arab states can link their actions to the SDGs. Notwithstanding the major variations in the contexts for civil society across the region, this framework may help to strengthen the credibility of CSOs in the eyes of state authorities and local societies.